Leadership in healthcare - Hrbáčová, Eliška; Bednářová, Martina; Pažitný, Peter, 1976-; Vysoká škola ekonomická v Praze. Fakulta managementu (2019)
The aim of thesis is to evaluate and compare various physician leadership competencies in the Czech healthcare environment. Theoretical part of the thesis reviews the literature regarding the topic of leadership. The methodology used in this thesis is a survey based upon a questionnaire by Gallagher Integrated Healthcare Strategies. The procedure was to distribute the survey among the highest number of medical personals across the healthcare system in the Czech Republic. Conclusion of the thesis consists of recommendations for leadership competency development.
Vedoucí práce: Martina Bednářová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2019
Obsahuje bibliografii
Rok obhajoby 2019
Keywords: management; zdravotní péče; řídící práce; manažerské dovednosti; management [obor bakal. práce]; bakalářské práce; management; health care; leadership; management skills; bachelor's theses